SLC2A9 rs16890979 reduces uric acid absorption by kidney organoids - Wu, Shouhai; Li, Chuang; Li, Yizhen; Liu, Junyi; Rong, Cuiping; Pei, Hongfei; Li, Xiong; Zeng, Xiang; Mao, Wei (Frontiers in Cell and Developmental Biology, 2024)
Introduction: The excretion and absorption of uric acid (UA) by the kidneys helps regulate serum UA levels. GLUT9, encoded by SLC2A9, is mainly expressed in the renal tubules responsible for UA absorption. SLC2A9 polymorphisms are associated with different serum UA levels. However, the lack of proper in vitro models has stalled research on the mechanisms of single nucleotide polymorphisms (SNPs) that affect UA metabolism in human urate transporters. Methods: In this study, we constructed a gene-edited human embryonic stem cells-9 (ESC-H9) derived kidney organoid bearing rs16890979, an SLC2A9 missense mutation with undetermined associations with hyperuricemia or hypouricemia. Kidney organoids derived from ESC-H9 with genetical overexpression (OE) and low expression (shRNA) of SLC2A9 to serve as controls to study the function of SLC2A9. The function of rs16890979 on UA metabolism was evaluated after placing the organoids to urate-containing medium and following histopathological analysis. Results: The kidney organoids with heterozygous or homozygous rs16890979 mutations showed normal SLC2A9 expression levels and histological distribution, phenotypically similar to the wild-type controls. However, reduced absorption of UA by the kidney organoids with rs16890979 mutants was observed. This finding together with the observation that UA absorption is increased in organoids with SLC2A9 overexpression and decreased in those with SLC2A9 knockdown, suggest that GLUT9 is responsible for UA absorption, and the rs16890979 SNP may compromise this functionality. Moreover, epithelial-mesenchymal transition (EMT) was detected in organoids after UA treatment, especially in the kidney organoid carrying GLUT9OE, suggesting the cytobiological mechanism explaining the pathological features in hyperuricosuria-related renal injury. Discussion: This study showing the transitional value of kidney organoid modeling the function of SNPs on UA metabolism. With a defined genetic background and a confirmed UA absorption function should be useful for studies on renal histological, cellular, and molecular mechanisms with this organoid model.